NUTRIENT PROFILE AND IN VITRO GAS PRODUCTION ANALYSIS OF SOME NEWER FEED RESOURCES FOR DAIRY CATTLE - V. Mozhiarasi; A. Bharathidhasan; K. Shivashankar; P. Shete; Ch. Manikumar (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The present study was carried out to assess the nutrient composition and in vitro gas production analysis of some commonly available newer feed resources to use them as a conventional feed for dairy cattle. Eight different newer feed resources namely Pomegranate peel, Sugarcane bagasse, Orange peel, Mango seed kernel, Banana leaves, Carrot pulp waste, Neem oil cake and Poultry manure were collected and screened for their nutrient composition, in vitro gas production analysis and their gross energy values. The results showed that the crude protein and crude fiber content of newer feed resources ranged from 1.98 % to 20.88 % and 4.93 % to 25.36 % respectively. The ether extract and total ash content ranged from 0.48 % to 11.36 % and 1.77% to 19.11 % respectively. The levels of nitrogen free extract ranged from 41.4 % to 77.3 %. The Neutral Detergent Fibre and Acid Detergent Fibre content ranged from15.21 % to 78.15 % and 14.27 % to 57.78 % respectively. The total gas production of carrot pulp waste recorded the highest values (48.29 ml) and banana leaves recorded the lowest values (2.47 ml) among the newer feed resources. The highest and lowest gross energy value was recorded in neem oil cake (4926 kcal/kg) and poultry manure (3235 kcal/kg) respectively. It was concluded that the ingredients contained appreciable level of dietary nutrients make them to substitutes for the conventional feed sources for dairy cattle.